Numerical Study of Wind Loads on Y Plan-Shaped Tall Building Using CFD - Goyal, Pradeep K.; Kumari, Sonia; Singh, Shivani; Saroj, Rahul Kumar; Meena, Rahul Kumar; Raj, Ritu (Salehan Institute of Higher Education, 2022)
The increase in the population is at an exponential rate, and the available land is in the form of irregular shapes. That is why irregular shapes are very commonly built. Wind load increases with respect to height, so wind load evolution is necessary for such high-rise structures. Wind forces majorly depend on the plan's cross-sectional shape. Therefore, for an irregular shape, an investigation is needed for tall buildings. This paper demonstrates a detailed study on velocity stream line, external pressure coefficients, pressure distribution on the surfaces of the building and the turbulence kinetic energy for the Y-shaped plan for tall buildings under wind excitation for wind incidence angles of 0o to 180o. k- turbulence model is utilized to solve the problem using computational fluid dynamics techniques in ANSYS for terrain category II as per IS: 875 (Part3), 2015. Wind ward faces in all building models show positive pressure distribution, while the leeward faces are under the effect of negative pressure distribution. Wind load can be reduced on building models by modifying the corners, such as chamfering, rounding, and double recessed. The variation of pressure distribution on different faces of a